2007
DOI: 10.1614/0890-037x(2007)21[378:eorhui]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Residual Herbicides Used in the Last Post-directed Application on Weed Control and Cotton Yield in Glyphosate- and Glufosinate-resistant Cotton

Abstract: Field experiments were conducted to evaluate weed control and cotton response to glyphosate or glufosinate applied alone or with residual herbicides applied in the last POST-directed application (LAYBY) in glyphosate- and glufosinate-resistant cotton. Glyphosate (0.86 kg ae/ha) or glufosinate (0.47 kg ai/ha) were applied alone over the top of glyphosate- or glufosinate-resistant cotton early POST (EPOST) followed by (fb) late POST (LPOST) fb one of the herbicides applied either alone or with a residual herbici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Furthermore, 5% injury was observed 7, 14, and 28 d after glufosinate was applied to eight-leaf cotton. These results are consistent with those of Blair-Kerth et al 2001, Everman et al (2007), Gardner et al (2006, and Koger et al (2007) who observed , 2% injury to LL cotton following glufosinate applications at multiple application timings.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, 5% injury was observed 7, 14, and 28 d after glufosinate was applied to eight-leaf cotton. These results are consistent with those of Blair-Kerth et al 2001, Everman et al (2007), Gardner et al (2006, and Koger et al (2007) who observed , 2% injury to LL cotton following glufosinate applications at multiple application timings.…”
Section: Resultssupporting
confidence: 91%
“…The time of weed emergence is one of the most important factors in determining the magnitude of crop yield losses (Myers et al 2004); therefore, herbicide application timing should be planned based on weed emergence and weed size to provide season-long weed control that results in maximum soybean yields (Hilgenfeld et al 2004). Several studies reported that the addition of a residual herbicide with POST herbicide later in the season improves weed control, and reduces weed seed production, as well as providing an additional mode of action that reduces selection pressure for weed resistance (Gonzini et al 1999;Tharp and Kells 2002;Koger et al 2007). Thus, micro-encapsulated acetochlor will be a good additional tool to include in PRE or POST herbicide program in soybean.…”
Section: Canadian Journal Of Plant Sciencementioning
confidence: 99%
“…It was important to investigate the effects of pre-plant and pre-emergence herbicide mixtures on weeds in cotton. Since cotton plants had a slower and longer life cycle compared to other plants, the risk of phytotoxicity to herbicides is high (Koger et al, 2007). For this reason, the effect of the active ingredients on the weeds as well as the effect on yield should be taken into consideration in the studies of herbicides (Streibig and Jensen 2000).…”
Section: Introductionmentioning
confidence: 99%